Sales Transaction Result Analysis for Increase Prediction of Income - Sucipto Sucipto (Universitas Darussalam Gontor, 2018)
The use of data that has long stored in the information system can be utilized to know information that supports decision-making activities. One of them is sales transaction data. During this time, the case of sales transaction data is rarely analyzed to be taken into consideration when taking a decision, such as analyzing the transaction data. The prediction analysis of the transaction should analyze the inflation factors that affect earnings. It is predicted that inflation will lead to an increase in the price of basic necessities which can also lead to employers tend to raise the price of products to be sold. Therefore, this research focuses to analyze sales transaction data at a restaurant. Where the data used is data that has been stored for 3 years within the period 2015-2017. The purpose of this study is to determine the quality comparison of sales predictions of sales between years with regard to inflation based on changes in selling prices. The result of the study is known that the prediction of goods sold with actual data in the following year is quite significant and the prediction of income is not affected by the inflation based on price comparison.